Design of nanosystems for melanoma treatment - Farasatkia, Asal (2024)
Melanoma is a prevalent and concerning form of skin cancer affecting millions of individuals worldwide. Unfortunately, traditional treatments can be invasive and painful, prompting the need for alternative therapies with improved efficacy and patient outcomes. Nanosystems offer a promising solution to these obstacles through the rational design of nanoparticles (NPs) which are structured into nanocomposite forms, offering efficient approaches to cancer treatment procedures. A range of NPs consisting of polymeric, metallic and metal oxide, carbon-based, and virus-like NPs have been studied for their potential in treating skin cancer. This review summarizes the latest developments in functional nanosystems aimed at enhancing melanoma treatment. The fundamentals of these nanosystems, including NPs and the creation of various functional nanosystem types, facilitating melanoma treatment are introduced. Then, the advances in the applications of functional nanosystems for melanoma treatment are summarized, outlining both their benefits and the challenges encountered in implementing nanosystem therapies.